Hospital attendance and admission trends for cardiac diseases during the COVID-19 outbreak and lockdown in Greece. (October 2020) - Oikonomou, E.; Aznaouridis, K.; Barbetseas, J.; Charalambous, G.; Gastouniotis, I.; Fotopoulos, V.; Gkini, K.-P.; Katsivas, A.; Koudounis, G.; Koudounis, P.; Koutouzis, M.; Lamprinos, D.; et al.
Abstract: Objectives: The coronavirus disease 2019 (COVID-19) outbreak, along with implementation of lockdown and strict public movement restrictions, in Greece has affected hospital visits and admissions. We aimed to investigate trends of cardiac disease admissions during the outbreak of the pandemic and possible associations with the applied restrictive measures. Study design: This is a retrospective observational study. Methods: Data for 4970 patients admitted via the cardiology emergency department (ED) across 3 large-volume urban hospitals in Athens and 2 regional/rural hospitals from February 3, 2020, up to April 12 were recorded. Data from the equivalent (for the COVID-19 outbreak) time period of 2019 and from the postlockdown time period were also collected. Results: A falling trend of cardiology ED visits and hospital admissions was observed starting from the week when the restrictive measures due to COVID-19 were implemented. Compared with the pre–COVID-19 outbreak time period, acute coronary syndrome (ACS) [145 (29/week) vs. 60 (12/week),  −59%, P  < 0.001], ST elevation myocardial infarction [46 (9.2/week) vs. 21 (4.2/week),  −54%, P  = 0.002], and non-ST elevation ACS [99 cases (19.8/week) vs. 39 (7.8/week),  −60% P  < 0.001] were reduced at the COVID-19 outbreak time period. Reductions were also noted for heart failure worsening and arrhythmias. The ED visits in the postlockdown period were significantly higher than in the COVID-19 outbreak time period (1511 vs 660; P  < 0.05). Conclusion: Our data show significant drops in cardiology visits and admissions during the COVID-19 outbreak time period. Whether this results from restrictive measures or depicts a true reduction of cardiac disease cases warrants further investigation. Highlights: The coronavirus disease 2019 (COVID-19) outbreak has led to an unprecedented health system overload. The restrictive measures in Greece resulted in a low number of COVID-19 cases. Hospital visits and cardiovascular events have diminished after implementation of restrictive measures. Acute coronary syndromes reduced by approximately 55%, despite limited incidence of COVID-19. The multifactorial etiology of this finding should be thoroughly investigated.